Iatrogenic fistula in Luapula province. Inequitable distribution of good surgical skills - Shanzi, Aubrev (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To highlight the burden of iatrogenic fistula in Luapula province and associated factors. Methods: Data were collected from February 2017 to February 2018 using a structured questionnaire. At least two surgeons determined whether the fistula was iatrogenic or not from history, examination and finding during fistula surgery. Results: Hundred and sixty six (166) fistula surgeries were done in the period under study; 18% of these fistula were classified as iatrogenic; 61.5% of the iatrogenic fistula were a result of caesarean section and 38.5% from hysterectomies. The type of surgical injuries included vault fistula (19.2%), ureteric fistula (26.9%), Juxta-cervical fistula (50%) and utero-vesico fistula (3.8%). Conclusions: Iatrogenic fistula is a common among fistula patients in Luapula province. It is unacceptable that the most disabling obstetric morbidity should so frequently result from poor surgical skills. Training surgeons and other health care staff in emergency obstetric care is essential to preventing new cases of iatrogenic fistula. Keywords: fistula, iatrogenic, emergency obstetric care